1998
DOI: 10.1073/pnas.95.12.6728
|View full text |Cite
|
Sign up to set email alerts
|

Two-domain reconstitution of a functional protein histidine kinase

Abstract: In prokaryotes, in the absence of protein serine/threonine/tyrosine kinases, protein histidine kinases play a major role in signal transduction involved in cellular adaptation to various environmental changes and stresses. Histidine kinases phosphorylate their cognate response regulators at a specific aspartic acid residue with ATP in response to particular environmental signals. In this His-Asp phosphorelay signal transduction system, it is still unknown how the histidine kinase exerts its enzymatic function.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
81
0
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(86 citation statements)
references
References 30 publications
(16 reference statements)
4
81
0
1
Order By: Relevance
“…In this class the catalytic and ATP-binding domain is separated in two regions (37). The A domain is involved in the dimerization, phosphotransfer, and phosphatase activity, while the B domain binds ATP (38,39). These histidine kinases transfer a phosphoryl group on an aspartate residue in the cognate regulator protein (OmpR in the case of EnvZ).…”
Section: Discussionmentioning
confidence: 99%
“…In this class the catalytic and ATP-binding domain is separated in two regions (37). The A domain is involved in the dimerization, phosphotransfer, and phosphatase activity, while the B domain binds ATP (38,39). These histidine kinases transfer a phosphoryl group on an aspartate residue in the cognate regulator protein (OmpR in the case of EnvZ).…”
Section: Discussionmentioning
confidence: 99%
“…The cytoplasmic domain has been dissected further into a linker domain (residues 180-222), domain A (dimerization and histidine-containing domain, residues 223-289) and domain B (catalysis-assisting and ATP-binding domain, residues 290-450) [6]. Domain A and domain B are central to the autophosphorylation function of EnvZ, which mediates coupling between the environmental sensing and activation of OmpR by phosphorylation of an aspartate residue.…”
Section: Introductionmentioning
confidence: 99%
“…NMR structures of both domain A and domain B have been solved (4,5). Biochemical analysis has revealed that the domain A of the EnvZ is responsible for the dimerization, phosphotransfer and phosphatase functions, and domain B binds ATP and catalytically assists the enzymatic function of domain A (3,6). The spatial arrangement between these two domains appears to be crucial for the modulation of EnvZ enzymatic activities (6).…”
mentioning
confidence: 99%
“…It is composed of a periplasmic domain, transmembrane domains, and a cytoplasmic domain (1,2). The cytoplasmic domain has been further dissected into three subdomains, the linker region, domain A, and domain B, in which the latter two form the catalytic core of EnvZ, harboring both kinase and phosphatase functions (3). NMR structures of both domain A and domain B have been solved (4,5).…”
mentioning
confidence: 99%